De l'adoption et de « l'abandon » d'un enfant légitime ou l'art de tourner la loi - Castelli, Mireille (Les Cahiers de droit, 1977)
At issue in these two cases are, first, the statutory requirements which relate to the abandonment and the adoptability of a legitimate child and, second, the statutory requirements which determine the jurisdiction of the Social Welfare Court with respect to the child's custody. The statutory conditions relative to the abandonment of the child during one year by the father could not be met because the father had been refused custody of the child which he had sought before the expiration of the required period of time. Moreover, there is the question whether the Social Welfare Court was competent to pass on the matter since the child was not adoptable and therefore had been irregularly placed.